If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -15 = 9x + 9 Reorder the terms: -15 + -3x = 9x + 9 Reorder the terms: -15 + -3x = 9 + 9x Solving -15 + -3x = 9 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -15 + -3x + -9x = 9 + 9x + -9x Combine like terms: -3x + -9x = -12x -15 + -12x = 9 + 9x + -9x Combine like terms: 9x + -9x = 0 -15 + -12x = 9 + 0 -15 + -12x = 9 Add '15' to each side of the equation. -15 + 15 + -12x = 9 + 15 Combine like terms: -15 + 15 = 0 0 + -12x = 9 + 15 -12x = 9 + 15 Combine like terms: 9 + 15 = 24 -12x = 24 Divide each side by '-12'. x = -2 Simplifying x = -2
| m+4=1 | | 2x^2+3-5=0 | | 6p=-96 | | n/8=-12 | | 30=12n-18 | | -5+n=-23 | | -632=4g | | -9j-10=62 | | 8=-12+x | | 2=4h-14 | | 5w-3w= | | -6=v-4 | | 6x+8=2x-28 | | 18+5.50x=y | | J+434=-376 | | (-4x-5)=-125 | | Y=(x^2+5)2x+1 | | 2x^2+5x+15=0 | | 49=16+3j | | -10=x-17 | | -7-5(8n*8)=193 | | 6=d/7 | | -2x=-26 | | 4x^2+3x-76=0 | | 9+5.50x=y | | -3h-4.2=55-11h | | n-16=-8 | | 15+2h=9 | | s/49=10/14 | | 56+8w=2w+16 | | 35=7+4s | | 4x+3y=22 |